Estudio de empleabilidad y situación laboral en los graduados de Cultura Física. - Ricardo Fernando, Mejía Pérez (2022)
ABSTRACT In recent years, there has been a drastic increase in unemployment. The concern for stable employment for university graduates is increasing in the population of Higher Education and disability in the labor market. The significant problems of university students in finding a job according to their area have transformed it into a susceptible problem that can sometimes be seen in a situation derived from social exclusion. Employability is based on the peculiarities and individual capacities that facilitate a way to adapt to the situations of each one, both professional and personal, the needs of the labor market requirements. Potentially, the research is treated from the aspect offered by university education at the level of academic training to obtain a job successfully. A significant part of unemployment has been generated in the labor market by not having an adequate preparation for which interests have been formed. Standard in all companies and institutions, which are the proper skills and strategies at work, will significantly influence formal and informal procedures for acquiring a job in the labor market (Aguilar, 2003). The employment situation should be highlighted, which affects those professionals who are already in the labor market, for such are those workers who must worry not only about a good job performance but also be alarmed to keep their source of work due to the constant competition for a stable job (Ibarra, 2015) Keywords: Employability, Labor Situation, Physical Culture graduates. Firmado electrónicamente por: ANA ELIZABETH MALDONADO LEON Reviewed by: Ms.C. Ana Maldonado León ENGLISH PROFESSOR C.I.060197598